2000
DOI: 10.1175/1520-0442(2000)013<4196:meffwa>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Multimodel Ensemble Forecasts for Weather and Seasonal Climate

Abstract: In this paper the performance of a multimodel ensemble forecast analysis that shows superior forecast skills is illustrated and compared to all individual models used. The model comparisons include global weather, hurricane track and intensity forecasts, and seasonal climate simulations. The performance improvements are completely attributed to the collective information of all models used in the statistical algorithm.The proposed concept is first illustrated for a low-order spectral model from which the multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
359
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 578 publications
(375 citation statements)
references
References 34 publications
6
359
0
5
Order By: Relevance
“…This result is to be expected as improvement in skill with larger ensemble sizes has been demonstrated (e.g. Krishnamurti et al, 2000). The area-averaged values of Figure 4 show that the ECHAM4.5-RegCM3 system is marginally outscored by the small-ensemble raw GCM and MOS simulations (the nested system has lower correlation values and higher RMSE values than the other two systems).…”
Section: Simulation Skill Levels For the 10-year Periodsupporting
confidence: 54%
See 1 more Smart Citation
“…This result is to be expected as improvement in skill with larger ensemble sizes has been demonstrated (e.g. Krishnamurti et al, 2000). The area-averaged values of Figure 4 show that the ECHAM4.5-RegCM3 system is marginally outscored by the small-ensemble raw GCM and MOS simulations (the nested system has lower correlation values and higher RMSE values than the other two systems).…”
Section: Simulation Skill Levels For the 10-year Periodsupporting
confidence: 54%
“…Krishnamurti et al, 2000). As raw GCM and GCM-MOS skill improves with an increased number of ensemble members, it can also be expected that the GCM-RCM skill will improve.…”
Section: Discussionmentioning
confidence: 99%
“…The superensemble approach is a recent contribution to the general area of weather and climate prediction developed at FSU (Krishnamurti et al, 1999;Krishnamurti et al, 2000a). A variant of the conventional superensemble formulation, the synthetic superensemble (FSUSSE), was created to improve the skill in seasonal climate forecasts Krishnamurti et al, 2005).…”
Section: Florida State University Synthetic Superensemble (Fsusse) Mementioning
confidence: 99%
“…This process was necessary since the data length, i.e. numbers of forecasts, were still quite small for the optimal development of a training phase as discussed in Krishnamurti et al (2000a). In Figure 5, the forecasts produced by the FSUSSE algorithm show lower RMS errors (higher skill) than those of the multi-model ensemble mean and the models comprising the ensemble for the overall average of all years.…”
Section: Precipitation Forecast Skill Of the Fsussementioning
confidence: 99%
“…In this study, we mainly consider the effect of model biases and how MME may improve the simulations. MME has been applied to both coupled earth system models (Krishnamurti et al 2000;Barnston et al 2003;Palmer et al 2004;Kirtman et al 2014) and offline LSMs (Guo et al 2007), and it was found that results from MME are generally better than those from most individual models. An unexplored problem is whether a land model ensemble can improve climate simulations in coupled land-atmosphere models and how effective the land model ensemble is compared to the traditional MME across the coupled models.…”
Section: Introductionmentioning
confidence: 99%